Algorithms for Sensor Systems 7th International Symposium on Algorithms for Sensor Systems, Wireless Ad Hoc Networks and Autonomous Mobile Entities, ALGOSENSORS 2011, Saarbrücken, Germany, September 8-9, 2011, Revised Selected Papers - Erlebach, Thomas; Nikoletseas, Sotiris; Orponen, Pekka (Computer Communication Networks and Telecommunications,, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the 7th International Workshop on Algorithms for Sensor Systems, Wireless Ad Hoc Networks, and Autonomous Mobile Entities, ALGOSENSORS 2011, held in Saarbrücken, Germany, in September 2011. The 16 revised full papers presented together with two invited keynote talks were carefully reviewed and selected from 31 submissions. The papers are organized in two tracks: sensor networks, covering topics such as localization, lifetime maximization, interference control, neighbor discovery, self-organization, detection, and aggregation; and ad hoc wireless and mobile systems including the topics: routing, scheduling and capacity optimization in the SINR model, continuous monitoring, and broadcasting.